Xenoantigen Deletion and Chemical Immunosuppression Can Prolong Renal Xenograft Survival. Issue 4 (October 2018) - Adams, Andrew B.; Kim, Steven C.; Martens, Gregory R.; Ladowski, Joseph M.; Estrada, Jose L.; Reyes, Luz M.; Breeden, Cindy; Stephenson, Allison; Eckhoff, Devin E.; Tector, Matt; Tector, Alfred Joseph
Abstract : Objective: Xenotransplantation using pig organs could end the donor organ shortage for transplantation, but humans have xenoreactive antibodies that cause early graft rejection. Genome editing can eliminate xenoantigens in donor pigs to minimize the impact of these xenoantibodies. Here we determine whether an improved cross-match and chemical immunosuppression could result in prolonged kidney xenograft survival in a pig-to-rhesus preclinical model. Methods: Double xenoantigen (Gal and Sda ) knockout (DKO) pigs were created using CRISPR/Cas. Serum from rhesus monkeys (n = 43) was cross-matched with cells from the DKO pigs. Kidneys from the DKO pigs were transplanted into rhesus monkeys (n = 6) that had the least reactive cross-matches. The rhesus recipients were immunosuppressed with anti-CD4 and anti-CD8 T-cell depletion, anti-CD154, mycophenolic acid, and steroids. Results: Rhesus antibody binding to DKO cells is reduced, but all still have positive CDC and flow cross-match. Three grafts were rejected early at 5, 6, and 6 days. Longer survival was achieved in recipients with survival to 35, 100, and 435 days. Each of the 3 early graft losses was secondary to IgM antibody-mediated rejection. The 435-day graft loss occurred secondary to IgG antibody-mediated rejection. Conclusions: Reducing xenoantigens in donor pigs and chemical immunosuppression can be used to achieve prolonged renal xenograft survival in a preclinical model, suggesting that if a negative cross-match can be obtained for humans then prolonged survival could be achieved.